United Kingdom aid cuts: implications for financing health systems - Kaci Kennedy McDade; Wenhui Mao; Annalisa Prizzon; Ro W. Huang; Ro W. Huang; Osondu Ogbuoji; Osondu Ogbuoji (Frontiers Media S.A., 2023)
BackgroundThe United Kingdom (UK) used to be the second largest bilateral provider of official development assistance (ODA) for health. However, in 2021 the UK government cut its annual aid budget by 30%. We aim to understand how these cuts might affect financing for health systems in UK aid recipient countries.MethodsWe conducted a retrospective analysis of domestic and external funding for 134 countries that received UK aid for the 2019-2020 budget year. We grouped countries into two cohorts: those that continued to receive aid in 2020-2021 ("budget") and those that did not ("no budget"). Data was collected from publicly available datasets and we compared UK's ODA, UK's health ODA with total ODA, general government expenditures and domestic general government health expenditure to assess the donor dependency and donor concentration of budget and no budget countries.FindingsBudget countries are more reliant on external aid to finance their governments and health systems than no budget countries, with a handful of exceptions. While the UK does not appear to be a major ODA contributor among most no budget countries, it is in many budget countries. Two no budget countries in particular may be faced with health systems financing challenges given their high ratios of UK health aid to domestic government health expenditures: the Gambia (1.24:1) and Eritrea (0.33:1). Although "safe" for this budget cycle, a number of low-income countries in Sub-Saharan Africa have very high ratios of UK health aid to domestic government health expenditures, including South Sudan (3.15:1), Sierra Leone (0.48:1), and the Democratic Republic of Congo (0.34:1).InterpretationThe 2021-2022 UK aid cuts could have negative impacts in a few countries highly dependent on UK health aid. Its departure could leave these countries with rather large funding gaps to fill and create a more concentrated donor climate.